Budidaya Hijauan Pakan Ternak dan Pengolahan Pembuatan Silase di Desa Pringgasela Selatan, Kecamatan Pringgasela, Kabupaten Lombok Timur - Aldy Ramadhan; Akbar Prayoga; Chalida Alfany; Desti Suci Safitri; Indah Nahdiat Isrori; M. Teguh Jaka Satya Samudra Jati Suara; Muliadi Muliadi; Yulia Azmi Khotimah; Syahrial Ayub; Muhammad Zuhdi; Syamsuddin Syamsuddin (Jurnal Pengabdian Masyarakat Sains Indonesia, 2022)
South Pringgasela is one of the villages in the Pringgasela, East Lombok, West Nusa Tenggara, Indonesia. South Pringgasela Village is one of 10 villages and sub-districts in the Pringgasela sub-district. South Pringgasela village has a lot of forage, namely elephant grass (Pennisetum purpureum) and drast elephant grass (Pennisetum purpureum CV. Mott). The people of South Pringgasela mostly work as farmers and planters. Farmers in the village of South Pringgasela still use the traditional method. Therefore we provide training in the manufacture of fermented feed in the form of silage. Silage is animal feed that has a high water content, processed through a fermentation process with the help of micro-organisms. The process is carried out under anaerobic conditions or without oxygen, either with the addition of or without the addition of preservatives. With this silage making training, it aims to introduce livestock technology to farmers in South Pringgasela village, especially in the Kedondong area. Keywords: Silage, Pennisetum purpureum CV. Mott, P., Sotuh Pringgasela